Risk Perception in Pregnant Adolescents in the “Rafael Valdés” Policlinic in 2009 - Melissa Serra Ruíz; Rosa María Alonso Uría; Miguel Serra Valdés (Medisur)
Background: pregnancy in adolescence is commonly associated with higher medical risk, psychological problems and social disadvantages. Female adolescents tend to be ignorant on the risks of pregnancy at such age. Objective: to identify the risk perception in pregnant adolescents of the “Rafael Valdés” policlinic. Method: a prospective, descriptive study was conducted at the ‘’Rafael Valdés” policlinic in Cotorro, Habana, from January 1st to December 31st, 2009. It included 79 pregnant adolescents. Variables analyzed: age, educational level, current educational and marital status. Data were collected through direct interview. A questionnaire was also applied in order to assess risk perception in the group of adolescents. Data were processed in Excel, thus determining frequencies and percents. Results: 89, 9 % of adolescents were between 15 and 19 years old, 91, 5 % were single or had unstable partners and 74, 4 % began having sexual relationships after they were 15 years old. 49, 9 % of these adolescents had abandoned their studies. Most of them referred to know about contraception, sexuality and pregnancy risks. They had family support and pregnancy was booked on time. Nevertheless, there was no correspondence with the reasons exposed to continue with pregnancy. Conclusion: the process of orientation and education of adolescents on reproductive health and sexuality issues should be systematic and constitutes our responsibility.